Culture of Nursing School: Students' Perceptions. (12th February 2015) - Kantek, Filiz; Baykal, Ulku; Altuntas, Serap
Abstract: School culture is a powerful structure that facilitates understanding the behaviors of the participants through their school life. A positive and effective school culture brought about numerous benefits such as improving the commitment to the school, creating trust and preventing conflicts. In this study, perceptions of school culture among students enrolled in schools of nursing were investigated. The study is a descriptive one, which was performed with the participation of 625 students enrolled in four schools that offer nursing education. A "personal information form" and a "school culture scale" were used for data collection. The findings revealed that instructor-student relations subcategory of the scale (X=2.04) was the most positively perceived cultural characteristic for the students. It was also observed that student perception differ with respect to schools (p<.05) and there was a positive correlation between students' satisfaction about their schools and their perception of school culture. The study sets forth that students' perception of school culture positively contributes to their satisfaction with the school; therefore nursing students' perception of school culture should be improved. In future studies, the factors that influence nursing students' perception of school culture should be a more detailed examination.